2021
DOI: 10.1186/s42358-021-00175-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of homocysteine with ankylosing spondylitis: a systematic review and meta-analysis

Abstract: Background Hyperhomocysteinemia is associated with autoimmune diseases such as ankylosing spondylitis (AS), systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA). Current findings regarding plasma/serum homocysteine (HCY) levels in AS patients are inconsistent. This study aims to systematically evaluate the association between circulating HCY levels and AS. Methods Online electronic databases (PubMed, Web of Science, Embase, ScienceDire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The 5,10-methylenetetrahydrofolate reductase (MTHFR) gene is located in chromosome 1p36.3, encoding a key rate-limiting, regulatory enzyme in folate and homocysteine metabolism, which catalyzes the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate (131). The MTHFR rs1801133 (ala222Val) SnP, which is located in exon 4, has been found to be significantly associated with both aS and endometriosis (81)(82)(83). it has been previously suggested that polymorphisms in the MTHFR gene may result in alterations in gene expression levels and protein function, thus leading to an abnormal metabolism of 5,10-methylenetetrahydrofolate (82,83).…”
Section: Shared Genetic Polymorphisms and Biological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5,10-methylenetetrahydrofolate reductase (MTHFR) gene is located in chromosome 1p36.3, encoding a key rate-limiting, regulatory enzyme in folate and homocysteine metabolism, which catalyzes the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate (131). The MTHFR rs1801133 (ala222Val) SnP, which is located in exon 4, has been found to be significantly associated with both aS and endometriosis (81)(82)(83). it has been previously suggested that polymorphisms in the MTHFR gene may result in alterations in gene expression levels and protein function, thus leading to an abnormal metabolism of 5,10-methylenetetrahydrofolate (82,83).…”
Section: Shared Genetic Polymorphisms and Biological Mechanismsmentioning
confidence: 99%
“…The MTHFR rs1801133 (ala222Val) SnP, which is located in exon 4, has been found to be significantly associated with both aS and endometriosis (81)(82)(83). it has been previously suggested that polymorphisms in the MTHFR gene may result in alterations in gene expression levels and protein function, thus leading to an abnormal metabolism of 5,10-methylenetetrahydrofolate (82,83). Thus, the c677T missense mutation, which has been characterized as a thermally unstable one, probably influences the thermostability and activity of MHTFr protein, while it has been also reported that the rs1801133 T allele results in elevated plasma homocysteine levels, which, in combination with endothelial injury and vascular inflammation, may result in the development of cardiovascular disease, a well-known comorbidity of endometriosis (13,132).…”
Section: Shared Genetic Polymorphisms and Biological Mechanismsmentioning
confidence: 99%